Cover Picture. Issue 3 (18th June 2021) - Unknown
Abstract : Based on the various appropriate chemical and physical characterization and analysis, Yu and his coworkers provide sufficient evidence for the fact that the victuals packaging materials, especially polystyrene foam containers, can release microplastics (MPs) during daily usage. MPs have various sizes and irregular shapes, which have potential threats to ecosystems and human health. Abstract : Based on the various appropriate chemical and physical characterization and analysis, Yu and his coworkers provide sufficient evidence for the fact that the victuals packaging materials, especially polystyrene foam containers, can release microplastics (MPs) during daily usage. MPs have various sizes and irregular shapes, which have potential threats to ecosystems and human health.